Banks’ performance based on liquidity risk analysis / Nurul Syazwani Abdul Azis - Abdul Azis, Nurul Syazwani (2015)
Recent financial crisis raised the issue of understanding the liquidity risk of financial assets and institutions. In this study, the research is focusing on the banks’ performance based on liquidity risk analysis. The purpose of the study is to study the relationship between dependent variable and independent variable and identify which factor has the most significant influence towards the movement of banks’ capital. The dependent variable is Banks’ Capital meanwhile the independent variable are Deposit, Cash and Non-Performing Loan. This study use secondary data from 2010 to 2014 (monthly) from report Bank Negara Malaysia (BNM). The data is tested using Single Linear Regression and Multiple Linear Regression.